In vivo regulation of Fim Gene transcription in uropathogenic escherichia coli - Ding, Hua (My University, 2014)
Uropathogenic Escherichia coli (UPEC) is the primary cause of human urinary tract infections. Type 1 pili of UPEC allow adherence to uroepithelial cells. Expression of type 1 pili is affected by phase variation, where a 314-bp DNA element (called fimS) switches between Phase-ON and Phase-OFF orientations as a consequence of binding by two sitespecific recombinases FimB and FimE. In this study, we created three fim-lux operon transcriptional fusions and moved them into the clinical UPEC isolate NU149. Growth in acidic medium reduced transcription of three fim genes (fimA, fimB and fimE) compared to growth in neutral pH medium. In a low pH/high osmolarity environment, expression from all three fim genes was markedly decreased compared to the expression in growth media without added NaCl. When NU149 containing each fim-lux fusion was used to infect murine urinary tracts, fimA and fimB expression were high in murine bladders, but transcription of both genes was markedly lower at the fifth day post-inoculation in murine kidneys. In contrast, fimE expression was lower than either fimA or fimB over a five-day post-inoculation period in either UPEC bladders or kidneys. Our results suggest in vivo environmental factors in different niches affect fim gene expression by UPEC that infect the murine urinary tract.
Keywords: Escherichia coli infections--Research; Urinary tract infections--Research; Medical microbiology--Research